Strengthening Religious Moderation through the Integration of Digital Literacy in Islamic Religious Education Learning in the Digital Era - Iman Asrori; Omar Khaled (CV. Mitkom Indotama, 2026)
This study explores the integration of digital literacy into Islamic Religious Education (PAI) to strengthen religious moderation amid the challenges of the digital era. Religious moderation, defined as a balanced and tolerant approach to faith, faces obstacles from the rapid spread of hate speech, disinformation, and extremist narratives on social media, which exacerbate social polarization. Drawing on indicators such as national commitment, tolerance, anti-violence, and cultural accommodation, the research argues for revitalizing PAI curricula with digital awareness to equip students with critical thinking and filtering skills for online religious content. Employing a qualitative approach with case studies from Indonesian secondary schools, data were collected through interviews, observations, and document analysis involving educators and students. Findings reveal that conventional PAI models insufficiently address digital threats, leading to vulnerabilities in youth paradigms. The integration of digital literacy enhances moderation by promoting constructive online interactions and resistance to divisive narratives, resulting in improved inclusivity and harmony.The study recommends policy updates for PAI curricula, including mandatory digital literacy modules, and suggests further research on long-term impacts in diverse educational contexts. This contributes to national efforts in fostering adaptive, moderate religious attitudes for sustainable social cohesion